2017
DOI: 10.1016/j.bbmt.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Adult Umbilical Cord Blood Transplantation Using Myeloablative Thiotepa, Total Body Irradiation, and Fludarabine Conditioning

Abstract: Treatment related mortality (TRM) remains elevated in adult patients undergoing umbilical cord blood (UCB) transplantation, including an early rise in TRM suggestive of excessive toxicity associated with the standard myeloablative total body irradiation (TBI), fludarabine, and cyclophosphamide regimen. In an attempt to reduce regimen-related toxicity, we previously studied a modified myeloablative regimen with total body irradiation (1350 cGy) and fludarabine (160 mg/m2); TRM was decreased but neutrophil engra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…A series of studies have shown that TT is added to modified BuCy2 37 , MEL is added to FB 38 , Flu or Ara-C is added to the CyTBI regimen 1,5,11,39,40 , and a conditioning regimen composed of TT, TBI, and fludarabine 9 shows improved engraftment and survival in UCBT. These alternative enhanced conditioning regimens have become preferable protocols for UCBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies have shown that TT is added to modified BuCy2 37 , MEL is added to FB 38 , Flu or Ara-C is added to the CyTBI regimen 1,5,11,39,40 , and a conditioning regimen composed of TT, TBI, and fludarabine 9 shows improved engraftment and survival in UCBT. These alternative enhanced conditioning regimens have become preferable protocols for UCBT.…”
Section: Discussionmentioning
confidence: 99%
“…Graft failure (GF) and delayed engraftment restrict the application of umbilical cord blood transplantation (UCBT). Engraftment is successful in approximately 80%-90% of patients with UCBT [1][2][3][4][5][6][7][8][9][10] , and the remaining 10%-20% of patients do not become engrafted. It has always been believed that the limiting factor in UCBT is the low number of hematopoietic stem cells (HSCs) in cord blood units (CBUs); therefore, various strategies have been explored to increase the number of HSCs [11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Серед альтернативних кріопротекторних агентів використовують етиленгліколь, 1,2-пропіленгліколь, поліетиленоксид (ПЕО-1500, ПЕО-400), ПВП, гідроксицелюлозу, дисахариди (сахарозу, мальтозу, трегалозу), а також макромолекули декстрану, гідроксиетилового крохмалю тощо. Їх застосовують як основні кріопротектори, так і в комбінації з низькими дозами ДМСО [1,4,12,38,119]. Так, протягом останніх двох десятиліть багато уваги було приділено такому дисахариду, як трегалоза, яка володіє унікальними властивостями: сприяє ефективності формування склоподібного стану льоду, підтримує термодинамічну стабільність клітинних мембран, пригнічує ліпідний фазовий перехід та розділення ліпідів під час заморожування [43,123].…”
unclassified
“…As various data demonstrate, the minimum dose threshold for a single transplantation is (2.0-3.0) × 10 7 , and for double transplantation it made (1.5-2.0) × 10 7 per kg of the recipient's weight of each of the UCB units [4,39]. In particular, the Eurocord working group does not recommend the use of units, containing less than 3 × 10 7 NCs per 1 kg of the recipient's weight (according to the data obtained before freezing) [40,105].…”
mentioning
confidence: 99%